What is the taste of the others? Ethics at the table between tastes and disgust - Migliore, Tiziana (E|C, 2020)
This article elaborates a semiotics of disgust starting from a research on the relationship between gastronomy and ethics. Our hypothesis is that ethics has always found in gastronomy, which has a scale of values where the good is at the top and the bad at the bottom. Food at the table is an allegory built by men, a great Gedankenexperiment, to say what others taste like, with the hope that they taste good or that they can become good. Or in the opposite situation, the rotten, like in the Perishables series (2005) by Pinar Yolacan, with the effects of disgust that derive from it. The kitchen elevates us from the condition of mortals, disgusted at the thought of "eating dust and becoming dust" (Genesis 3, 14-19).